2012
DOI: 10.3109/03091902.2012.733056
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of transmembrane protein fused in lipid bilayer membranes supported on porous silicon

Abstract: This article investigates a device made from a porous silicon structure supporting a lipid bilayer membrane (LBM)fused with Epithelial Sodium Channel protein. The electrochemically-fabricated porous silicon template had pore diameters in the range 0.2~2 µm. Membranes were composed of two synthetic phospholipids: 1,2-diphytanoyl-sn-glycero-3-phosphoserine and 1,2-diphytanoyl-sn-glycero-3-phosphoethanolamine. The LBMwas formed by means of the Langmuir-Blodgett and Langmuir-Schaefer techniques, at a monolayer sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…[48,49] demonstrated the same LB/LS technique to create the artificial phospholipid membranes. This technique offers the advantage of tightly packing the lipid molecules, hence resulting in a bilayer membrane that is as strong and tight as possible.…”
Section: Dynamic Structure and Formation Of Lipid Bilayer Membrane (Lbm)mentioning
confidence: 99%
See 3 more Smart Citations
“…[48,49] demonstrated the same LB/LS technique to create the artificial phospholipid membranes. This technique offers the advantage of tightly packing the lipid molecules, hence resulting in a bilayer membrane that is as strong and tight as possible.…”
Section: Dynamic Structure and Formation Of Lipid Bilayer Membrane (Lbm)mentioning
confidence: 99%
“…At low pH, lipid membrane spreading over a planar surface is favorable, regardless of the net charge on the bilayer [49]. The major advantage of using solid supports is to achieve high robustness and stability of the phospholipid bilayer membrane.…”
Section: Dynamic Structure and Formation Of Lipid Bilayer Membrane (Lbm)mentioning
confidence: 99%
See 2 more Smart Citations
“…The height (1.7 nm) of the protrusions in bilayers was consistent with the modeled size of the sombrero component, which was structurally predicted to extend from the membrane by approximately the same distance. These observations suggested that Bot1 was incorporated in DMPC liposomes essentially uniformly with its N terminus directed to their exterior surface (Supplemental (Sanganna Gari et al, 2013) and of the epithelial sodium channel in a lipid bilayer membrane (Tantawi et al, 2013).…”
Section: Bot1 Protrudes 17 Nm Above the Bilayer Surfacementioning
confidence: 99%